Increased vascular O-GlcNAcylation augments reactivity to constrictor stimuli — Vasoactive Peptide Symposium - Lima, Victor V; Giachini, Fernanda R.C., MSc; Carneiro, Fernando S., MSc; Carneiro, Zidonia N; Fortes, Zuleica B., PhD; Carvalho, Maria Helena C., PhD; Webb, R. Clinton, PhD; Tostes, Rita C., PhD (Journal of the American Society of Hypertension, 2008)
Abstract O-linked N-acetylglucosaminylation (O-GlcNAcylation) plays a role in many aspects of protein function. Whereas elevated O-GlcNAc levels contribute to diabetes-related end-organ damage, O-GlcNAcylation is also physiologically important. Because proteins that play a role in vascular tone regulation can be O-GlcNAcylated, we hypothesized that O-GlcNAcylation increases vascular reactivity to constrictor stimuli. Aortas from male Sprague-Dawley rats and C57BL/6 mice were incubated for 24 hours with vehicle or PugNAc (O-GlcNAcase inhibitor, 100 μM). PugNAc incubation significantly increased O-GlcNAc proteins, as determined by Western blot. PugNAc also increased vascular contractions to phenylephrine and serotonin, an effect not observed in the presence of Nω -nitro- L -arginine methyl ester or in endothelium-denuded vessels. Acetylcholine-induced relaxation, but not that to sodium nitroprusside, was decreased by PugNAc treatment, an effect accompanied by decreased levels of phosphorylated endothelial nitric oxide synthase (eNOS)Ser-1177 and AktSer-473 . Augmented O-GlcNAcylation increases vascular reactivity to constrictor stimuli, possibly due to its effects on eNOS expression and activity, reinforcing the concept that O-GlcNAcylation modulates vascular reactivity and may play a role in pathological conditions associated with abnormal vascular function.